Performance Comparison of Symmetric and Offset Reflector Antennas Adaptively Illuminated by Novel Triple Mode Feedhorn - Satish K. Sharma; Mukund R. Thyagarajan (International Journal of Antennas and Propagation)
Parabolic symmetric and offset reflector antennas adaptively illuminated using a novel triple-mode feedhorn (TE11+TM01+TE21) with different mode combinations and impedance and radiation performances are presented. The combination of the radiating modes in a feedhorn with proper amplitude and fixed phase values helps in electronically pointing the main beam of the radiating patterns such as that obtained in a beam-steering antenna with limited beam-scan range. This type of radiation performance virtually creates a displaced phase center location for the feedhorn, which, consequently, adaptively illuminates the reflector antenna surface. Impedance-matching bandwidths are preserved for both reflector antennas similar to the case of feedhorn alone. The copolarization gain and peak cross-polarization levels are far better with the offset reflector antenna than the symmetric reflector antenna. Such reflector antennas find applications in ground moving target indicator (GMTI) and space based radars. The investigation results are solely computed using FEKO full-wave analysis tool.